2007
DOI: 10.1590/s0034-70942007000100004
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do tratamento prévio com lidocaína, paracetamol e lidocaína-fentanil por via venosa na dor causada pela injeção de propofol: estudo comparativo

Abstract: RESUMOEl-Radaideh KM -Efeitos do Tratamento Prévio com Lidocaína, Paracetamol e Lidocaína-Fentanil por Via Venosa na Dor Causada pela Injeção de Propofol. Estudo Comparativo. JUSTIFICATIVA E OBJETIVOS:Foi realizado estudo duplamente encoberto, aleatório, para avaliar a eficácia do tratamento prévio, por via venosa, com lidocaína, paracetamol (Perfalgan) ou lidocaína associada ao fentanil na redução da dor causada pela injeção de propofol. MÉTODOS:Imediatamente após a oclusão venosa com torniquete de borracha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…There was not any significant difference between the first and the third group (P > 0.05), but the difference between the forth (placebo) and the other three groups was significant (P > 0.05). There was also a significant difference between the groups receiving lidocaine and the one who received paracetamol (P < 0.05).In conclusion, Khaled reported that lidocaine can relive the propofol injection pain up to 70% (13). …”
Section: Discussionmentioning
confidence: 78%
“…There was not any significant difference between the first and the third group (P > 0.05), but the difference between the forth (placebo) and the other three groups was significant (P > 0.05). There was also a significant difference between the groups receiving lidocaine and the one who received paracetamol (P < 0.05).In conclusion, Khaled reported that lidocaine can relive the propofol injection pain up to 70% (13). …”
Section: Discussionmentioning
confidence: 78%
“…According to our results, Paracetamol reduces propofol injection pain up to 28.57%, which is slightly different from the results of other studies. In Radaideh’s study, 54% of the paracetamol group had no pain (5). Borazan et al investigated the effects of lidocaine with different doses of paracetamol on the reduction of propofol injection pain.…”
Section: Discussionmentioning
confidence: 99%
“…In a study which was carried out in September 1999 by Ramer and colleagues, it was determined that the pain severity after propofol injection without anesthesia, was approximately 70%, which is not associated with the size of catheter (IV) or propofol infusion rate. In addition, the results of Radaideh’s study in 2007 on 200 patients, indicated that 4 cc of lidocaine 1% reduces the pain of propofol injection by 68 % (5). The results of these studies are consistent with our findings, indicating that lidocaine reduces the pain of propofol injection up to 69.64%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a much higher reduction than our study findings (51.35% pain free), which might be related to the additional use of diclofenac 50 mg and fentanyl 2.5 U/kg before propofol injection. El-Radaideh studied the effect of 40 mg paracetamol pretreatment on propofol injection pain and concluded that 54% of the patients were pain free [15]. Paracetamol has been used for propofol injection pain in doses ranging from as low as 40 mg to 1 g. However, we found that 1 g of IV paracetamol in combination with lidocaine pretreatment is superior to lidocaine pretreatment alone in reducing pain associated with propofol administration.…”
Section: Discussionmentioning
confidence: 83%